Predictors of poor outcome in treatment of patients with pyoinflammatory otogenic and rinosinusogenic intracranial complications - A. A. Krivopalov; Yu. K. Janov; A. Yu. Shcherbuk; Yu. A. Shcherbuk; A. N. Rubin; S. A. Artyushkin; Z. N. Shardanov (Вестник хирургии имени И.И. Грекова)
OBJECTIVE. The authors would like to reveal preoperative and intraoperative predictors of lethal outcome in patients with otogenic and rhinosinusogenic pyoinflammatory intracranial complications. The study assessed an efficacy of specialized medical care of this category of patients. MATERIAL AND METHODS. Тhis research included 303 patients (199 (65,68 %) men and 104 (34,32 %) women) aged from 39,3 ± 17,4 years on average who underwent operation concerning intracranial pyoinflammatory oto- and rinosinusogenic complications in multidisciplinary hospitals of different subjects of the Russian Federation at the period from 2000 to 2014. RESULTS. Multiple logit regression analysis of predictors of lethal outcome showed the presence of higher number of factors and errors which influenced on treatment during preoperative period. These factors and errors caused an extension of preoperative period and increase of unfavorable outcome. CONCLUSIONS. While planning the management of primary and specialized care, doctors should take into account the identified predictors for patients of this category.